2021
DOI: 10.3390/ijfs9030033
|View full text |Cite
|
Sign up to set email alerts
|

Are Cryptocurrencies a Backstop for the Stock Market in a COVID-19-Led Financial Crisis? Evidence from the NARDL Approach

Abstract: The study investigates the safe haven properties and sustainability of the top five cryptocurrencies (Bitcoin, Ethereum, Dash, Monero, and Ripple) and gold for BRICS stock markets during the COVID-19 crisis period from 31 January 2020 to 17 September 2020 in comparison to the precrisis period from 1 January 2016 to 30 January 2020, in a nonlinear and asymmetric framework using Nonlinear Autoregressive Distributed Lag (NARDL) methodology. Our results show that the relationship dynamics of stock market and crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 38 publications
2
21
0
1
Order By: Relevance
“…Fourth, the comovement patterns over the longer investment horizons (>128 days) reveal encouraging findings. The stock-Bitcoin coherence heatmaps corroborate the findings of [2,7] and [28] as they show the heat turns blue or even dark blue in some cases. The results indicate that Bitcoin can serve as a safe haven against the G7 stock markets during the pandemic [29], specifically for investors holding the cryptocurrency for a longer investment horizon.…”
Section: Wavelet Coherence Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Fourth, the comovement patterns over the longer investment horizons (>128 days) reveal encouraging findings. The stock-Bitcoin coherence heatmaps corroborate the findings of [2,7] and [28] as they show the heat turns blue or even dark blue in some cases. The results indicate that Bitcoin can serve as a safe haven against the G7 stock markets during the pandemic [29], specifically for investors holding the cryptocurrency for a longer investment horizon.…”
Section: Wavelet Coherence Resultssupporting
confidence: 76%
“…Similarly, ref. [7] have discovered Bitcoin as a safe haven against equities in Brazil, South Africa, and Russia during the pandemic. Meanwhile, Dash and Ripple show safe haven properties against all BRICS stock markets during the pandemic (31 January 2020 to 17 September 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Jeribi et al ( 2021 ) studied the relationship dynamics of stock markets and crypto-currency returns both in the short and long run with a special focus on changes during the COVID-19 crisis period. Their results indicated that Dash and Ripple are found to be a safe haven for stock markets before the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The author found the time-varying linearity specification of the LMM (Tv-LMM) favorable in terms of modeling & forecasting performance of cryptocurrency price and CCI30 index. Jeribi et al (2021) examined the price data of Bitcoin, Ethereum, Dash, Monero, Ripple, and gold from January 31, 2020, to September 17, 2020, to compare the pre-crisis period from January 01, 2016, to January 30, 2020. They conclude that the short and long-term dynamics of the stock market and cryptocurrency returns are changing during the pandemic.…”
Section: Review Of Literaturementioning
confidence: 99%